Efektivitas Pengelolaan Dana Bantuan Operasional Sekolah (BOS) pada SD di Kecamatan Jambo Aye, Aceh Utara: Partisipasi Stakeholder Sebagai Variabel Moderasi - Muhammad Yusra; Nur Afni Yunita; Nurhasanah Nurhasanah; Arliansyah Arliansyah (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2021)
This research is intended to determine how much influence accountability and transparency have on the effectiveness of the management of School Operational Assistance (BOS) funds with Stakeholder Participation as a Moderation Variable in Elementary Schools (SD) in Tanah Jambo Aye District, Aceh Utara Regency. In this study, samples taken were all committees and treasurers of SD in Tanah Jambo Aye District, as many as 50 people. The data collection technique used in this study was to distribute questionnaires to all committees and treasurers of SD in Tanah Jambo Aye District, North Aceh Regency. The data analysis method used in this study is to use multiple linear regression analysis. The results of this study indicate that accountability and transparency have a positive and significant effect on the effectiveness of the financial management of BOS funds at elementary schools in Tanah Jambo Aye District, Aceh Utara Regency. Then stakeholder participation was able to moderate the accountability, transparency and effectiveness of the management of BOS funds at SD in Tanah Jambo Aye District, North Aceh Regency. It is hoped that all school parties concerned should always be open to issues of accountability, transparency in the management of School Operational Assistance funds.Keywords: Accountability, Transparency, Effectiveness of BOS Fund Management, Stakeholder Participation